Analysis of Students' Errors in Solving Mathematical Problems Based on Field Independent and Field Dependent Cognitive Styles - Virnanda, Lady's Intana; Lestari, Wahyu; Waluyo, Eko (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Errors made by students in solving mathematical problems remain a common issue encountered in the learning process. Cognitive styles, such as Field Independent (FI) and Field Dependent (FD), are believed to influence how students comprehend and solve mathematical problems. Based on this premise, this study aims to analyze students' errors in solving mathematical problems by taking into account their cognitive styles, namely Field Independent (FI) and Field Dependent (FD). This research was conducted at SMAN 1 Besuk using a qualitative descriptive method and involved six students selected based on the results of the Group Embedded Figures Test (GEFT). Data were collected through the GEFT, problem-solving tests, and interviews, then analyzed using Newman's Error Analysis Procedure. The findings show that students with an FI cognitive style typically made errors in process skills (17.13%) and in constructing final answers (20.00%). In contrast, students with an FD cognitive style frequently made errors in problem transformation (45.71%), process skills (57.14%), and final answers (65.71%). Several factors contributing to these errors include lack of accuracy, rushing through tasks, misinterpreting implicit information in the problems, and failing to recheck final answers. The study concludes that cognitive style influences both the types and frequency of errors students make when solving mathematical problems. These findings highlight the importance for educators to develop instructional strategies that are better aligned with students' cognitive styles to enhance learning effectiveness.